Evaluation of Metal Artifacts in Cone Beam Computed Tomography by Metal Supported Porcelain Crowns Using Different FOV and Localizations: An In Vitro Study - Numan Dedeoğlu; Yasin Yaşa (Mashhad University of Medical Sciences, 2020)
Introduction: Metal-supported porcelain crowns (MSPC) and bridge restorations may be present in the mouths of patients undergoing CBCT imaging. Artifacts that are caused by these MSPCs may adversely affect image quality. The aim of this study is to determine the effect of different FOV (field of view) and localization in FOV on metal artifacts caused by MSPC. Methods: Twenty MSPCs scanned with CBCT at central and peripheral localization at 18x16 and 8x8 cm FOV. The 2.5 mm periphery area of the MSPC cross-sectional image was evaluated. The metal artefact-area within this area was measured. Then, the artifact-area to total-area ratio was converted to form of a percentage. In addition to evaluation of crown periphery area, the lengths of the metal streaks artifacts were measured. The maximum linear dimension of the metal artifact was recorded from the crown margin for each MSPC in cross-sectional image in the bucco-lingual direction. All data collected were evaluated by Kruskal-Wallis analysis and Mann Whitney U test (P˂0,05). Results: No statistically significant differences were found in the artifacts-area measured (P=0.121). However, there was a statistically significant difference in linear dimension measurements of artifacts (P=0.000). In 18x16 cm FOV localization peripheral linear dimension measurements were higher than other FOV and localizations. Conclusion: Linear size artifacts of MSPC were found to be higher in peripheral positioning in wide FOV. However, according to this study, areas evaluated for metal artifacts caused by MSPCs are not affected by FOV and localization.